Integración del programa de doctorado en Ciencias Biológicas a la Red Iberoamericana de Biotecnología Isla Negra (RIABIN). - Lanio, María E.; Seeger, Michael; Pazos Santos, Isabel Fabiola (Cuban Journal of Biological Sciences / Revista Cubana de Ciencias Biológicas)
The RIABIN network, belonging to the Pablo Neruda program and approved as Ibero-American initiative by the XVII Ibero-American Meeting of Heads of State and Government held in Chile in November 2007, is currently integrated by sixteen universities from nine countries of the region. Since its foundation the network has had the mission of benefiting solidarity, multilateralism, and joint collaboration among institutions from different developmental level. The tutorial PhD program in Biological Sciences and the PhD curricular program in Molecular Biosciences of the Biological Faculty from the UH were included to the network RIABIN in December 2009. This integration has made possible stable and permanent relations with the rest of network members through interchanges of professors, research stay of PhD students and postgraduate courses. As consequence of this a set of connections and academic mobility have been structured among the different universities. The PhD program in Molecular Biosciences organized two courses at the UH: Proteomic (2011) and Immunotherapy and Vaccinology (2013) with the attendance of 20 specialists and more than 50 students from different countries of the region. On the other hand, during the last three years the PhD programs, in the tutorial and curricular versions, have graduated a total of 48 PhD students, a part of them benefited by academic activities that have been supported by the network RIABIN.